Effects of rates and application times of molybdenum on common bean crop - Berger, Paulo Geraldo; Vieira, Clibas; Araujo, Geraldo A de A. (Pesquisa Agropecuaria Brasileira, 1996)
Two experiments on molybdenum rates for bean crop were carried out in Viçosa and Coimbra, in the Zona da Mata area of Minas Gerais state, Brazil. A 2 x 5 factorial experiment in a randomized complete block design was utilized; factors were two cultivars (Ouro and Ouro Negro) and five rates of Mo (0, 15, 30, 60, and 120 g/ha). The micronutrient was applied as foliar spray, 25 days after plant emergence. Two experiments on application times of Mo in bean crop were also carried out; they included nine treatments: no Mo and 20 g/ha of Mo applied as foliar spray 7, 14, 21, 28, 35, 42, 49, and 56 days after plant emergence. Ouro Negro was the bean cv. utilized. All four experiments received a uniform application of 4-14-8 at the rate of 600 kg/ha. It was found that the highest bean yields were obtained with 80-90 g/ha of Mo. The best application time was 14 to 28 days after plant emergence.